The association of non-alcoholic fatty liver disease with thyroid peroxidase and thyroglobulin antibody: A new insight from SPECT-China study - Yi Chen; Ningjian Wang; Yingchao Chen; Qin Li; Bing Han; Chi Chen; Hualing Zhai; Yingli Lu (Taylor & Francis Group, 2018)
Non-alcoholic fatty liver disease (NAFLD) has been studied with inflammation and immune, but the link with thyroid autoimmunity is unreported. This study aimed to explore the direct association of NAFLD with thyroid autoimmune disease (AITD) among participants with normal thyroid stimulating hormone (TSH) levels. The data were obtained from a cross-sectional study (SPECT-China). A total of 7982 participants were enrolled. Participants underwent several checkups including peroxidase antibody (TPOAb), thyroglobulin antibody (TgAb), thyroid, and liver ultrasonography (US). The prevalence of NAFLD was higher in TPOAb and/or TgAb positive [TPO/TgAb (+)] group and TPOAb and/or TgAb together with US positive [TPO/TgAb (+) and US (+)] group for both genders. After full adjustment, binary logistic analysis showed the presence of NAFLD was positively associated with the serum level of TPOAb in men (p < .001) and TgAb in women (p = .001). Both TPO/TgAb (+) and TPO/TgAb (+) and US (+) were associated with an increased risk of NAFLD in both genders [TPO/TgAb (+): odds ratio (OR) 1.474, 95% confidence interval (CI) 1.102, 1.970 in men and OR 1.308, 95%CI 1.061, 1.612 in women; TPO/TgAb (+) and US (+): OR 1.796, 95%CI 1.143, 2.820 in men and OR 1.380, 95%CI 1.058, 1.801 in women]. Thus, we got a conclusion that the prevalence of NAFLD was positively associated with the level and the positivity of TPOAb and TgAb among participants with normal TSH levels. This is the first report suggesting that there might exist common pathways in the pathogenesis of NAFLD and thyroid autoimmunity.